Impact of textile dyes on health and ecosystem: a review of structure, causes, and potential solutions - Islam, Tarekul; Repon, Md.Reazuddin; Islam, Tarikul; Sarwar, Zahid; Rahman, Mohammed M. (Environmental science and pollution research international, 2023)
The rapid growth of population and industrialization have intensified the problem of water pollution globally. To meet the challenge of industrialization, the use of synthetic dyes in the textile industry, dyeing and printing industry, tannery and paint industry, paper and pulp industry, cosmetic and food industry, dye manufacturing industry, and pharmaceutical industry has increased exponentially. Among these industries, the textile industry is prominent for the water pollution due to the hefty consumption of water and discharge of coloring materials in the effluent. The discharge of this effluent into the aquatic reservoir affects its biochemical oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), total suspended solids (TSS), and pH. The release of the effluents without any remedial treatment will generate a gigantic peril to the aquatic ecosystem and human health. The ecological-friendly treatment of the dye-containing wastewater to minimize the detrimental effect on human health and the environment is the need of the hour. The purpose of this review is to evaluate the catastrophic effects of textile dyes on human health and the environment. This review provides a comprehensive insight into the dyes and chemicals used in the textile industry, focusing on the typical treatment processes for their removal from industrial wastewaters, including chemical, biological, physical, and hybrid techniques.